Fetuin-A level in type 2 diabetic patients: relation to microvascular complications - Nehal H Al-Said; Fatma M Taha; Ghada M Abdel-Aziz; Marwa S Abdel-Tawab (SpringerOpen, 2018)
Background Fetuin-A is a hepatic secretory protein that binds to insulin receptors and inhibits insulin resistance (IR) kinase activity as well as IR autophosphorylation in vivo and in vitro. Aim This study aimed to investigate fetuin-A levels in patients with type 2 diabetes mellitus (T2DM) and their relation to microvascular complications. Patients and methods This descriptive study was conducted on 160 patients. Group 1 included (n=40) diabetic patients without microvascular complications, group 2 (n=40) included diabetic patients with nephropathy, group 3 (n=40) included diabetic patients with retinopathy, and group 4 represented (n=40) healthy control. Serum fetuin-A and insulin were measured by enzyme-linked immunosorbent assay. Glucose was measured, and homeostasis model assessment for IR (HOMA-IR) was estimated. Results Fetuin-A levels were significantly higher in all T2DM groups compared with controls. There was a significant positive correlation between fetuin-A, insulin, and HOMA-IR in all studied groups. There was a significant positive correlation between fetuin-A and some of metabolic syndrome criteria in all diabetic patients. There were high significant increases in the mean levels of fetuin-A, insulin, and HOMA-IR in the diabetic patients with nephropathy group than other groups. There was a nonsignificant increase in fetuin-A levels in diabetic patients with retinopathy than the diabetics without microvascular complications. Conclusion Fetuin-A may be used as a marker for microvascular complications in T2DM, especially the diabetic nephropathy. Antifetuin drugs may be invented to delay diabetic microvascular complications.